The Effect of the Movement of a Passive Reflector on the Atomization of a Levitating Drop - Gaete-Garreton, L; Vargas-Hernandez, y; Meneses-Díaz, J; Cancino-Jaque, E (Institute of Physics, 2024)
This study investigates the instability of distilled water drops under acoustic levitation induced by the movement of a reflector toward the transducer. The experimental setup consisted of a passive concave reflector and a Langevin transducer in a uniaxial-resonance configuration. The experiment consists of achieving a stable levitation of the droplet and then moving the reflector constantly toward the transducer, shortening the distance h between them (reflector-transducer). All experiments were recorded using a high-speed camera to analyze the drop s behavior. The results revealed three distinct instabilities: radial atomization occurred when the drop volume (VD) was < 3.74 μ1, beyond which central atomization was observed. A third instability is observed when a low reflector velocity (Vr < 0.67 mm/s) is used, where the droplet exhibited modes of oscillation with pulsed central atomization. © 2024 Institute of Physics Publishing. All rights reserved.